Motivações para a escolha da licenciatura em matemática e pedagogia: um estudo com alunos da PUC/SP E UFMT - Souza, Levi de Oliveira (2010)
Education in Brazil has changed a lot in recent decades. Schools, previously aimed at the elite, are now for everyone. With more students, more schools and more well-trained teachers are needed to consolidate the process of democratization of education. The point is that at the same pace as the number of schools, students and teachers have increased, the quality of education provided in most schools in Brazil has decreased. Not only has the quality of education been decreasing in recent years but also the prestige and value of teachers in society as well as their socioeconomic status have been reduced. In this sense, this study, grounded on data available on the teaching career and its attractiveness in Brazil, seeks to know more about the following issues: the status of teachers in the structure of jobs, their socioeconomic condition, the relationship between the teachers education level and the level of education required, and the opinion of youngsters on the teaching career. Based on the analysis of these data, this research aims to define the profile of the students who choose teaching as a career as well as their motivation to become teachers of Mathematics or Pedagogy. Using data from the census of education and from the Brazilian National Examination on the Students Performance (ENADE), available on the site of the Anísio Teixeira National Institute of Educational Studies and Research (INEP), this research seeks to understand the reality of graduation courses in Mathematics and Pedagogy in Brazil, particularly, at the Pontifical Catholic University of São Paulo (PUC/SP) and the Federal University of the State of Mato Grosso (UFMT). Besides using the data mentioned above, a socioeconomic questionnaire was answered by the students of Mathematics and Pedagogy at PUC/SP and UFMT, where this study was carried out. Based on the analysis of the collected data, we found that the majority of these future teachers come from lower social classes (C and D) and the average number of children of most of their families is more than five. We could also notice that these teachers to be have High School degrees from public schools, do not have access to leisure activities, come mostly from families whose monthly income is up to three minimum wages, have parents with low schooling level, do not read more than three books a year and have faced a lot of difficulties in their school life. As far as motivation is considered, most of them have chosen teaching as a career because they want to become teachers in order to improve education and change the reality of schools in Brazil